A Narrative Review of Existing Options for COVID-19-Specific Treatments - Wasey Ali Yadullahi Mir; Abdul Hasan Siddiqui; Gautam Valecha; Shawn Patel; Fatima Ayub; Riddhi Upadhyay; Sana Ahmed Alhajri; Suman Gaire; Dhan Bahadur Shrestha (Advances in Virology)
The new coronavirus disease 2019 (COVID-19) was declared a global pandemic in early 2020. The ongoing COVID-19 pandemic has affected morbidity and mortality tremendously. Even though multiple drugs are being used throughout the world since the advent of COVID-19, only limited treatment options are available for COVID-19. Therefore, drugs targeting various pathologic aspects of the disease are being explored. Multiple studies have been published to demonstrate their clinical efficacy until now. Based on the current evidence to date, we summarized the mechanism, roles, and side effects of all existing treatment options to target this potentially fatal virus.